Математическая модель структурной эволюции общественных производительных сил - Повещенко, Г.; Чеховой, Ю. (Социология: теория, методы, маркетинг, 2001)
Mathematical model of social productive forces structural evolution is discussed, particularly with regard to evolution of social production of life. There are analyzed some methodological grounds and issues of mathematical modeling, like correlation between accuracy and complexity/simplicity of models. There are presented both conceptual model of social production of life (by V.Khmelko) and mathematical model developed according to the conceptual one.